Hubungan Aktivitas Fisik terhadap Sleep Quality pada Wanita Menopause - Ni Ketut Ari Putri; Ni Luh Nopi Andayani; I Putu Gde Surya Adhitya; Gede Parta Kinandana (KOLONI, 2026)
Physical activity is one of the factors that can influence sleep quality, particularly in menopausal women who experience various physiological changes due to declining estrogen levels. These hormonal changes can lead to sleep disturbances such as difficulty falling asleep, frequent awakenings during the night, and a decline in overall sleep quality. Poor sleep quality can impact the physical and psychological health, as well as the quality of life, of menopausal women. Therefore, non-pharmacological interventions are needed to help improve sleep quality, one of which is through regular physical activity tailored to individual conditions. This study aims to determine the relationship between physical activity and sleep quality among menopausal women in Banjar Anyar Gede and Kubu Alit Kedonganan. This study employed an analytical observational design with a cross-sectional approach involving 84 respondents selected using purposive sampling. Physical activity levels were measured using the International Physical Activity Questionnaire-Short Form (IPAQ-SF), while sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI). Data were analyzed using the Chi-Square test with a 95% significance level (α = 0.05). The results of the study indicate that most respondents engaged in moderate physical activity and had good sleep quality. Bivariate analysis revealed a significant association between physical activity and sleep quality in menopausal women (p = 0.001). Based on the study results, it can be concluded that higher levels of physical activity tend to be associated with better sleep quality in menopausal women.